“I am a Suffragist and a Socialist”: The Relationship between the British Socialist and Suffrage Movements, 1884-1914 - Muriel Pécastaing-Boissière (Revue Française de Civilisation Britannique)
Although the link between socialism and suffragism can be traced back to the Owenite and Chartist movements of the 1830s and 1840s, between 1884 and 1914, the new phase of the campaign for women’s suffrage coincided with the socialist revival, then the emergence of the Labour Party. The relationship between the socialist and suffrage movements intensified, with a significant overlap of their respective memberships. Yet, the issue of women’s suffrage has generally been overlooked by historians of British socialism, and one has to look mostly to feminist historians to assess the importance of the relationship between the socialist and suffrage movements before the First World War. After a brief reminder of the composition and evolution of both movements in 1884-1914, this article will study their divisions and alliances relating to their main two debates: class v. sex, and adult v. women’s suffrage.